1998
DOI: 10.4269/ajtmh.1998.58.137
|View full text |Cite
|
Sign up to set email alerts
|

Human antibody responses to Trypanosoma cruzi 70-kD heat-shock proteins.

Abstract: Heat-shock proteins of the 70-kD (hsp70) family are targets of humoral and cellular immune responses following bacterial or parasitic infections, including Chagas' disease. In the present study, we measured antibodies in human sera reactive with hsp70s from the cytoplasm (cy-hsp70), mitochondrion (mt-hsp70), and endoplasmic reticulum (grp78) of Trypanosoma cruzi. Of the three hsp70s tested, only grp78 detected T. cruzi infection in more than 90% of nontreated (NT) patients, with cy-hsp70 and mt-hsp70 detecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 40 publications
(61 reference statements)
0
26
0
3
Order By: Relevance
“…The function of this protein remains largely unknown, but it has been hypothesized that it participates in an acyl-calcium switch system (12), and this proposal is supported by experimental data showing a Ca 2ϩ -dependent conformational change (26). Since it was cloned for the first time, its utility in the diagnosis of T. cruzi infection has been well established (14,18,25,(33)(34)(35), including the possibility of using its gene sequence for PCR diagnosis (31). The rapid reduction of antibodies against calflagin in patients that respond to trypanocidal treatment has also been demonstrated, indicating that calflagin may be used in therapy follow-up (33).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The function of this protein remains largely unknown, but it has been hypothesized that it participates in an acyl-calcium switch system (12), and this proposal is supported by experimental data showing a Ca 2ϩ -dependent conformational change (26). Since it was cloned for the first time, its utility in the diagnosis of T. cruzi infection has been well established (14,18,25,(33)(34)(35), including the possibility of using its gene sequence for PCR diagnosis (31). The rapid reduction of antibodies against calflagin in patients that respond to trypanocidal treatment has also been demonstrated, indicating that calflagin may be used in therapy follow-up (33).…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, no Leishmania orthologs have been described up to now. Several studies on the diagnostic profile of this recombinant protein identified its use as a valuable antigen for the serological detection of the infection in the indeterminate phase (14,18,25,34,35) and for therapy evolution follow-up (33). Several works also established that sera from Leishmania spp.-infected individuals have low levels of cross-reactivity with T. cruzi calflagins (14,34,35).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Although important contributions have been made to better define their potential role as immunogens or diagnostic tools, no functional characterization has been defined for the majority of the described parasite molecules. [1][2][3][4][5][6][7][8][9][10][11][12][13] The immunological functions of calreticulin in mammals have been delineated to some extent, in particular as a chaperone molecule in the process of antigen presentation to CD8ϩ T cells. Thus, when ␤ 2 -microglobulin binds to the major histocompatibility complex (MHC) class I ␣ chain, the partially folded ␣␤ 2 -microglobulin heterodimer dissociates from calnexin and binds calreticulin.…”
Section: Introductionmentioning
confidence: 99%
“…The calcium binding protein of low molecular weight (Tc24) also had a good correlation with the CoML test (86%) (Krautz et al 1995). The heat-shock proteins, especially HP70, were proven to be reliable antigens to assess cure after chemotherapy and replaced the CoML test in the followup of treated patients (Krautz et al 1998). These antigens were successfully used in ELISA tests and showed a high correlation with the results of the CoML test when the same sera (from patients treated and cured) were used in parallel (Table V).…”
Section: Resultsmentioning
confidence: 99%